Cardiac reconstructions with allograft valves - Hopkins, R. A (Springer, 1989)
A major need of all cardiologists and surgeons involved with the application of allograft tissue to cardiac surgical reconstructions is met by this unique atlas. Step by step, it carefully describes the procedures involved in acquiring, sterilizing, and cryo-preserving allograft valves as well as the surgical technique used in left and right ventricular outflow tract reconstructions. All of the information needed to perform the reconstructions is given, including relevant references and applicable variations in method. Excellent illustrations accompany the description of surgical technique. All of the techniques are based on classic approaches, but assimilate the authors\' modifications arrived at through vast experience. The wealth of references, illustrations and expertise in this volume make it a valuable asset for all cardiac surgeons.
Keywords: srdce; kardiochirurgie; Cardiac Surgical Procedures; Heart; kardiochirurgické výkony